2016
DOI: 10.3166/rfg.2016.00074
|View full text |Cite
|
Sign up to set email alerts
|

Les cadres devraient-ils être « nomades » ?

Abstract: Les comportements effectifs des cadres montrent la persistance des trajectoires managériales et intra-organisationnelles : les cadres ne sont pas « nomades ». Pour compléter ces constats, on cherche ici à vérifier si les carrières « nomades » cumulent plus de gains que les autres. Une carrière « nomade » se définit, dans cet article, par le fait qu’elle déroge aux scripts de carrières institutionnalisés. L’échelle de qualité de carrière est utilisée pour mesurer les gains liés aux trajectoires. L’étude est com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The concept of a career script enables the reinscription of these experiences within an institutional environment (Gunz et al, 2011;Laudel et al, 2019). A script constitutes a set of rules and norms related to career progression that acts as an intermediary between the individual and the organization by delineating possible trajectories (Barley, 1989;Cohen & Duberley, 2015;Pralong & Perreti-Ndiaye, 2016). Arthur et al (1999) suggested that organizations are producers of representations that allow individuals to plan their careers.…”
Section: Mapping and Contextualizing Transnational Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a career script enables the reinscription of these experiences within an institutional environment (Gunz et al, 2011;Laudel et al, 2019). A script constitutes a set of rules and norms related to career progression that acts as an intermediary between the individual and the organization by delineating possible trajectories (Barley, 1989;Cohen & Duberley, 2015;Pralong & Perreti-Ndiaye, 2016). Arthur et al (1999) suggested that organizations are producers of representations that allow individuals to plan their careers.…”
Section: Mapping and Contextualizing Transnational Mobilitymentioning
confidence: 99%
“…Arthur et al. (1999) suggested that organizations are producers of representations that allow individuals to plan their careers. These representations, acting as scripts, reveal possible pathways for individuals.…”
Section: Mapping and Contextualizing Transnational Mobilitymentioning
confidence: 99%